Protein kinase A-mediated phosphorylation of HERG potassium channels in a human cell line - Wei, Zhang; Thomas, Dierk; Karle, Christoph; Kathöfer, Sven; Schenkel, Johannes; Kreye, Volker Armin; Ficker, Eckhard; Wible, Barbara A.; Kiehn, Johann (Chinese medical journal, 2002)
OBJECTIVE: To investigate the molecular mechanism of human ether-a-go-go-related gene (HERG) potassium channels regulated by protein kinase A (PKA) in a human cell line. - METHODS: HERG channels were stably expressed in human embryonic kidney (HEK) 293 cells, and currents were measured with the patch clamp technique. The direct phosphorylation of HERG channel proteins expressed heterologously in Xenopus laevis oocytes was examined by (32)P labeling and immunoprecipitation with an anti-HERG antibody. - RESULTS: Elevation of the intracellular cAMP-concentration by incubation with the adenylate cyclase activator, forskolin (10 micromol/L), and the broad range phosphodiesterase inhibitor, IBMX (100 micromol/L), caused a HERG tail current reduction of 83.2%. In addition, direct application of the membrane permeable cAMP analog, 8-Br-cAMP (500 micromol/L), reduced the tail current amplitude by 29.3%. Intracellular application of the catalytic subunit of protein kinase A (200 U/ml) led to a tail current decrease by 56.9% and shifted the activation curve by 15.4 mV towards more positive potentials. HERG WT proteins showed two phosphorylated bands, an upper band with a molecular mass of approximately 155 kDa and a lower band with a molecular mass of approximately 135 kDa, indicating that both the core- and the fully glycosylated forms of the protein were phosphorylated. - CONCLUSIONS: PKA-mediated phosphorylation of HERG channels causes current reduction in a human cell line. The coupling between the repolarizing cardiac HERG potassium current and the protein kinase A system could contribute to arrhythmogenesis under pathophysiological conditions.